Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1889)
Demorest's Family Magazine. November 1889. Vol. 26, no. 1. -- Ten Woman-Novelists of America -- Fiend or Fool? -- November -- From Ocean's Bed to Boudoir -- A Thanksgiving Turkey -- The "Angelus" -- That Last Reception on the "Nemo" -- Our Girls: Husbands, Lovers, and Friends -- Aids to Beauty: V. The Finger-Nails -- An Electrical Machine -- Home Art and Home Comfort: Crocheted Rug -- Smyrna Embroidery: With Designs -- Sanitarian: Diseases Incident to the Season; Rheumatism and Neuralgia -- The World's Progress -- The Site for the International Exhibition of 1892 -- "English, You Know!" -- Ophelia -- Chat -- What Woman are Doing -- Household: The Home Laboratory III. The Chemistry of Cleaning -- The Lunch-Basket -- Cooking for Thanksgiving -- Mirror of Fashions: Review of Fashions -- Description of Our Cut Paper Patterns -- Mrs. Sophia A Keyes: President of the Southern California Woman's Christian Temperance Union -- The Dangerous Fallacy of Local Option -- The "Third Party" in 1852: Why Parties and Principles are More Important than Candidates -- Medal Contest Notes -- Correspondence Club -- Spice Box
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print. Valdosta State University Archives and Special Collections. May 22, 2017.
Keywords: Women's History; Social History; Periodicals; Illustrated Periodicals; Magazine; 1800s; 19th Century; Dressmaking; Needlework; Children; Travel; Fashion; United States